Minimasi Biaya Distribusi pada UMKM Keset Samian dengan Metode VAM dan Modi - Abas; Nuriyanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Transportation methods are methods used to optimally manage the distribution of goods from suppliers to destinations. The method used is Vogel's Approximate Method (VAM) and Modified Distribution (MODI). This research aims to minimize distribution costs for Keset Samian MSMEs. Samian Doormat UMKM is a small and medium business engaged in the production of doormat crafts. The Samian Doors Umkm experiences problems in managing distribution costs efficiently which has a direct impact on business profits. This research uses primary and secondary data collection related to costs. distribution, demand, and production capacity. The data was analyzed using VAM to determine the initial optimal cost solution in allocating the distribution of doormat products. The results of the VAM method were further optimized using the MODI method to achieve minimal costs in the distribution of doormat products. The research results show that the VAM and MODI methods are able to reduce distribution costs significantly compared to the traditional methods currently used by the Samian Doormat MSMEs. Where from the initial cost of Rp. 4,250,000 to Rp. 2,843,500 which experienced a decrease in transportation costs of Rp. 1,406,500 or 33.09%. So the results of calculating transportation costs for UMKM Keset Samian are optimal and increase business profits.